2019
DOI: 10.3389/fimmu.2019.02777
|View full text |Cite
|
Sign up to set email alerts
|

Cell Intrinsic Deregulated ß-Catenin Signaling Promotes Expansion of Bone Marrow Derived Connective Tissue Type Mast Cells, Systemic Inflammation, and Colon Cancer

Abstract: Mast cells constitutively express ß-catenin and expand in solid tumors such as colon and skin cancer. However, the role of ß-catenin signaling in mast cells and the cause or effect of mast cell expansion and tumor growth has yet to be established. In earlier studies we used mast cell depletion and protease staining approaches, to provide evidence for a causative role of mast cells in small bowel polyposis, and related specific phenotypes and distributions of tumor infiltrating mast cells to stages of tumor gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Another study using the B16 murine melanoma model found that ILC2 cells expanded by IL‐33 promoted tumour growth by inhibiting the activation and cytotoxicity of NK cells [54]. In a spontaneous mouse model of colon cancer, Saadalla et al described increased numbers of ILC2 cells in colon adenomas as compared to adjacent healthy tissue, although the impact of these ILC2 cells on cancer progression was not addressed [55]. Consistent with ILC2 accumulation in colon cancer, IL‐33 expression was shown to be elevated in mouse intestinal polyps [56], and was also detected in human colon cancer epithelial cells [57, 58].…”
Section: Innate Lymphoid Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study using the B16 murine melanoma model found that ILC2 cells expanded by IL‐33 promoted tumour growth by inhibiting the activation and cytotoxicity of NK cells [54]. In a spontaneous mouse model of colon cancer, Saadalla et al described increased numbers of ILC2 cells in colon adenomas as compared to adjacent healthy tissue, although the impact of these ILC2 cells on cancer progression was not addressed [55]. Consistent with ILC2 accumulation in colon cancer, IL‐33 expression was shown to be elevated in mouse intestinal polyps [56], and was also detected in human colon cancer epithelial cells [57, 58].…”
Section: Innate Lymphoid Cellsmentioning
confidence: 99%
“…cancer progression was not addressed [55]. Consistent with ILC2 accumulation in colon cancer, IL-33 expression was shown to be elevated in mouse intestinal polyps [56], and was also detected in human colon cancer epithelial cells [57,58].…”
Section: Ilc2 Cells and Cancermentioning
confidence: 99%
“…Chronic activation of ß‐catenin in rodent MCs has been reported to be associated with the development of skin cancers. However, the molecular mechanism needs to be clarified 64 . Although an increased number of MCs and their positive correlation with the progression of tumors have been reported in the majority of papers, the accumulation of MCs in different tumor types may act in favor of a better prognosis.…”
Section: Mast Cell Involvement In the Pathology Of Nmscs: Sccmentioning
confidence: 99%
“…However, the molecular mechanism needs to be clarified. 64 Although an increased number of MCs and their positive correlation with the progression of tumors have been reported in the majority of papers, the accumulation of MCs in different tumor types may act in favor of a better prognosis. For instance, higher numbers of MCs in OSCC correlate negatively with lymph node metastasis.…”
Section: Lessons From Mice Modelsmentioning
confidence: 99%
“…In turn, MC directly promoted tumor cell proliferation [ 176 ]. Like stem cells, MC also express beta-catenin, an important pro-proliferative molecule that is activated in response to Wnt ligands secreted by colonic tumor cells [ 177 ]. Strikingly, the activation of beta-catenin in MCs was shown to induce the formation of colonic polyps.…”
Section: Type 2 Immune Cells In Crcmentioning
confidence: 99%